1998
DOI: 10.1111/1469-8986.3510023
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus context determines P3a and P3b

Abstract: P300 differences for target (.10), nontarget (.10), and standard tones (.80) were assessed using a three-stimulus oddball paradigm in which participants responded only to the target (n = 12). Target/standard (easy or difficult) and nontarget/standard (large or small) pitch differences were manipulated orthogonally. In all conditions, target tones elicited a parietal P300, which was affected only by the target/standard discrimination ease. Nontarget in the easy/large and difficult/small conditions elicited a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
101
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(123 citation statements)
references
References 42 publications
18
101
0
1
Order By: Relevance
“…Although this null result may have been influenced by statistical power (and increasing trial or sample size may have revealed higher speed or accuracy as a function of larger monetary reward), our current results point to the role of motivation as a possible modulating factor in the P3's role in reward processing, as reflected by the graded ratings on the subjective interest and excitement scales (45¢>1¢>0¢) (Figure 3). Note that although a parallel graded response was visually discernible in the P3 waveforms (Figure 2), it was not statistically significant (45¢>1¢=0¢), possibly due to low statistical power or the restricted distinctiveness between the low and no reward conditions (see (Comerchero & Polich, 1998) and (Katayama & Polich, 1998) for a positive relationship between P3 amplitude and stimulus distinctiveness). To overcome this limitation, future studies could compare additional or more disparate reward conditions (e.g., $2 vs. $1 vs. 10¢).…”
Section: Discussionmentioning
confidence: 90%
“…Although this null result may have been influenced by statistical power (and increasing trial or sample size may have revealed higher speed or accuracy as a function of larger monetary reward), our current results point to the role of motivation as a possible modulating factor in the P3's role in reward processing, as reflected by the graded ratings on the subjective interest and excitement scales (45¢>1¢>0¢) (Figure 3). Note that although a parallel graded response was visually discernible in the P3 waveforms (Figure 2), it was not statistically significant (45¢>1¢=0¢), possibly due to low statistical power or the restricted distinctiveness between the low and no reward conditions (see (Comerchero & Polich, 1998) and (Katayama & Polich, 1998) for a positive relationship between P3 amplitude and stimulus distinctiveness). To overcome this limitation, future studies could compare additional or more disparate reward conditions (e.g., $2 vs. $1 vs. 10¢).…”
Section: Discussionmentioning
confidence: 90%
“…This explanation is in accordance with our interpretation of the HIV-related P2 amplitude reduction. Lastly, task/stimuli differences may also account for the discrepant findings as the relative perceptual distinctiveness among stimuli in the oddball task can determine P3a and P3b amplitudes (Katayama and Polich, 1998). The current study employed a 3-stimulus oddball task with highly discrepant non-target stimuli (sound effect noises) and easily distinguished target and standard stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…For the central LPC, there are at least two possible interpretations: P3a and no-go P300. P3a has been reported to be a frontal/central positivity elicited by several types of infrequent non-target stimuli (e.g., Courchesne et al, 1975;Katayama and Polich, 1998;Squires et al, 1975), and is considered to reflect the attentional shift produced by the mismatch. On the other hand, it has been reported that infrequent non-target stimuli that are easily recognized as "typical" (i.e., not novel) could elicit another types of LPC with maximum amplitudes over the central/parietal area (e.g., Courchesne, 1978;Courchesne et al, 1978;Katayama and Polich, 1996), which is sometimes referred to as no-go P300.…”
Section: Discussionmentioning
confidence: 99%